Management of private tubewells in a conjunctive use environment: a case study in the Mananwala Distributary Command Area, Punjab, Pakistan - Malik, S.M.; Strosser, P. (International Irrigation Management Institute, 1993)
This paper analyzes the tubewell data collected by IIMI-Pakistan over a period of 4 years. While the main emphasis remains on the operation of private tubewells, public tubewells and canal water supplies are included in the analyses to give a more comprehensive picture of the conjunctive use environment, a characteristic of most of the irrigated areas of the Punjab, Pakistan.